2013
DOI: 10.5433/1679-0359.2013v34n5p2211
|View full text |Cite
|
Sign up to set email alerts
|

The chemical properties of soil for alfalfa production after biofertiliser application

Abstract: The objective of this study was to evaluate the use of biofertilisers for the production of alfalfa shoot, root and nodule dry matter, and also, to evaluate the chemical properties of the soil. This study was conducted in the greenhouse of the Support Department, Animal Production and Health, Faculty of Veterinary Medicine/UNESP, Araçatuba -SP, from May to October 2010. The experimental design was completely randomised with six biofertiliser doses (0, 25, 50, 100, 200 and 400 m 3 ha -1) and five replicates. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Tanzania, observed SDWY was higher in the fertilized vessels with the highest biofertilizer rates in the third harvest occurring at 84 days after planting. Lemes et al (2013) studying the increasing bovine biofertilizer rates of alfalfa observed a linear increase in SDWY and RDWY. Silva Neto et al (2010) verified that SDWY of Megarthysus maximum cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanzania, observed SDWY was higher in the fertilized vessels with the highest biofertilizer rates in the third harvest occurring at 84 days after planting. Lemes et al (2013) studying the increasing bovine biofertilizer rates of alfalfa observed a linear increase in SDWY and RDWY. Silva Neto et al (2010) verified that SDWY of Megarthysus maximum cv.…”
Section: Discussionmentioning
confidence: 99%
“…Soares Filho et al (2015) applied bovine biofertilizer to Tierra Verde bermudagrass (Cynodon dactylon (L.) Pers.) and Lemes et al (2013) to alfalfa (Medicago sativa), and the authors observed that it positively influenced the soil and leaf chemical contents and the nutritional quality of alfalfa (Lemes et al 2016). In Brazil, there is a considerable part of cattle production conducted in intensive rearing systems, resulting in a large volume of liquid slurry, with high fertilizer potential that, when properly stored and correctly used, can supply nutrients to the plants and improve soil chemical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of absorbed N increases linearly with the application of biofertilizers but is proportional to biomass increases in the aerial part of alfalfa (LEMES et al, 2013), showing that absorbed N was diluted in the dry shoot mass without significant increases in concentrations, featuring the dilution effect (JARREL; BEVERLY, 1981). Similar results were found by Araujo et al (2011) A biofertilizer dose of 400 m 3 ha -1 resulted in highest K absorptions (Figure 1), and the concentration was within the range established by Moreira et al (1997) and Raij et al (1997).…”
Section: Resultsmentioning
confidence: 99%
“…The direct effect of the application of bovine manure biofertilizers in the soil is the increase in the availability of nutrients (Alves et al, 2009;Cavalcante et al, 2011a;Lemes et al, 2013;Oliveira et al, 2014), as a function of the soluble minerals (Tables 1, 2 in the organic input and by the direct action of the pathogen on its host (Santos, 1992;Marrocos et al, 2012;Shivlata & Satyanarayana, 2015).…”
Section: Applications and Edaphic Effects Of The Biofertilizermentioning
confidence: 99%
“…, and 3). In an area cultivated with bell pepper,Alves et al (2009) concluded that the Vairo and Agrobio biofertilizers raised the pH and the concentrations of phosphorus, potassium, and soil organic matter, whereasLemes et al (2013), while cultivating lettuce, verified that the Vairo biofertilizer raised the contents of calcium and magnesium in the soil Oliveira et al (2014). observed increases in phosphorus, potassium, calcium, magnesium, and soil organic matter promoted by the Supermagro, even with superiority to the contents of a soil fertilized with NPK.…”
mentioning
confidence: 99%